2018
DOI: 10.1016/j.envexpbot.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Monoterpene responses to interacting effects of drought stress and infection by the fungus Heterobasidion parviporum in two clones of Norway spruce (Picea abies)

Abstract: A B S T R A C TTo study simultaneous biotic and abiotic stress effects on monoterpene mediated defence response, four-year-old seedlings of two clones of Picea abies (c386: "relatively resistant" c386; c171: "relatively susceptible" clone 171) were inoculated with an isolate of rot fungus Heterobasidion parviporum and simultaneously subjected to a drought stress recovery cycle. Fungal growth into the wood was generally higher in well-watered (W) than in drought-stressed (D) plants. As predawn water potential d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 76 publications
1
10
1
1
Order By: Relevance
“…They observed increased pathogen growth in well-watered seedlings [33], which is in contrast to our results. However, the duration of water availability treatment (22 days) in Madmony et al [33] was much shorter than in this study (105 days). These results highlight the need for well-established inoculation studies for this pathosystem, when studying effects of abiotic disturbances.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…They observed increased pathogen growth in well-watered seedlings [33], which is in contrast to our results. However, the duration of water availability treatment (22 days) in Madmony et al [33] was much shorter than in this study (105 days). These results highlight the need for well-established inoculation studies for this pathosystem, when studying effects of abiotic disturbances.…”
Section: Discussioncontrasting
confidence: 99%
“…This result is consistent with Linnakoski et al [2], who found that blue stain fungi E. polonica caused greater necrosis and mortality in P. abies seedlings with low water availability compared to those with high water availability. Madmony et al [33] inoculated H. parviporum into two-year-old branches of two different Norway spruce clonal ramets (4-year old) and subjected them to well-watered and drought environments. They observed increased pathogen growth in well-watered seedlings [33], which is in contrast to our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Availability of such markers will greatly facilitate screening for trees with high tolerance to root disease, while decreasing the required cost and labor. Since we collected tree samples before inoculation for terpene compounds and gene expression analysis, we emphasize that this work is distinct from other studies (Zamponi et al 2007;Madmony et al 2018) where samples were collected post-inoculation. When trees are wounded, the production of secondary metabolic compounds is induced, which interferes with the identification of trees that are naturally genetically resistant.…”
Section: Introductionmentioning
confidence: 99%
“…O composto terpinolene ou isoterpinene ou terpinolen ou alpha-terpinolene; 1,4(8)-pmenthadiene é um monoterpeno que em situações de estresse hídrico teve sua emissão diminuída e em tratamentos com estresse biótico ela foi aumentada em plantas de Picea abies (MADMONY et al, 2018). Neste trabalho foi encontrado terpinolene em plantas de couve e…”
Section: Tabela De Vida De Plutella Xylostella Em Laboratóriounclassified